(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The effect of nitrogen (0, 80, 120, and 160 kg/ha from urea) and sulphur (0, 20, 40, and 60 kg/ha from gypsum) fertilization on N and S uptake and yield performance of onion (var. BARI Piaz-1) was studied in the research field of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during rabi seasons of 2002-2003 and 2003-2004. The experiment was laid out in a randomized complete block design under factorial arrangement with three replications. Addition of nitrogen and sulphur fertilizers exerted significant influence on the number of leaves/plant, plant height, diameter of bulb, single bulb weight, and yield of onion. The uptake of N and S by bulb also significantly responded to the application of nitrogen and sulphur. The highest yield of onion and the maximum uptake of N and S were recorded by the combined application of 120 kg N and 40 kg S/ha with a blanket dose of 90 kg P2O5, 90 kg K2O, and 5 kg Zn/ha plus 5 tons of cowdung/ha. The antagonistic effect of nitrogen and sulphur on the uptake of N and S by bulb, yield components, and yield of onion was observed only when they were applied together at higher rates of nitrogen (160 kg/ha) and sulphur (40kg/ha). DOI: http://dx.doi.org/10.3329/bjar.v32i3.543 Bangladesh J. Agril. Res. 32(3) : 413-420, September 2007